NDR1 increases NOTCH1 signaling activity by impairing Fbw7 mediated NICD degradation to enhance breast cancer stem cell properties - Ling-Ling Wang; Xiao-Yun Wan; Chun-Qi Liu; Fei-Meng Zheng (BMC, 2022)
Abstract Background The existence of breast cancer stem cells (BCSCs) causes tumor relapses, metastasis and resistance to conventional therapy in breast cancer. NDR1 kinase, a component of the Hippo pathway, plays important roles in multiple biological processes. However, its role in cancer stem cells has not been explored. The purpose of this study was to investigate the roles of NDR1 in modulating BCSCs. Methods The apoptosis was detected by Annexin V/Propidium Iodide staining and analyzed by flow cytometry. BCSCs were detected by CD24/44 or ALDEFLUOR staining and analyzed by flow cytometry. The proliferation ability of BCSCs was evaluated by sphere formation assay. The expression of interested proteins was detected by western blot analysis. The expression of HES-1 and c-MYC was detected by real-time PCR. Notch1 signaling activation was detected by luciferase reporter assay. Protein interaction was evaluated by immunoprecipitation. Protein degradation was evaluated by ubiquitination analysis. The clinical relevance of NDR1 was analyzed by Kaplan-Meier Plotter. Results NDR1 regulates apoptosis and drug resistance in breast cancer cells. The upregulation of NDR1 increases CD24low/CD44high or ALDEFLUORhigh population and sphere-forming ability in SUM149 and MCF-7 cells, while downregulation of NDR1 induces opposite effects. NDR1 increased the expression of the Notch1 intracellular domain (NICD) and activated the transcription of its downstream target (HES-1 and c-MYC). Critically, both suppression of Notch pathway activation by DAPT treatment or downregulation of Notch1 expression by shRNA reverses NDR1 enhanced BCSC properties. Mechanically, NDR1 interactes with both NICD or Fbw7 in a kinase activity-independent manner. NDR1 reduces the proteolytic turnover of NICD by competing with Fbw7 for NICD binding, thereby leading to Notch pathway activation. Furthermore, NDR1 might function as a hub to modulate IL-6, TNF-α or Wnt3a induced activation of Notch1 signaling pathway and enrichment of breast cancer stem cells. Moreover, we find that the elevation of NDR1 expression predictes poor survival (OS, RFS, DMFS and PPS) in breast cancer. Conclusion Our study revealed a novel function of NDR1 in regulating BCSC properties by activating the Notch pathway. These data might provide a potential strategy for eradicating BCSC to overcome tumor relapses, metastasis and drug resistance.